If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -2y = 1 Combine like terms: 3y + -2y = 1y 1y = 1 Solving 1y = 1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '1'. y = 1 Simplifying y = 1
| 18=0.9(x-1) | | x+2x+4=21 | | -2/3s-1=56 | | 30=.666666667p | | 14T^2-3T-2=0 | | 2y^2-7y-1=0 | | 15-2y=20 | | 2x-16=180 | | X(12+x)=38 | | (7x-3)/(x-5)0 | | X^2+4x+4=2x+19 | | 0.75(2x-3)-.05(6-x)=1.5x+3 | | 3x+-1=5 | | (4t^3/7n^3)^4 | | 8z=11.2 | | 7-(4-x)=8 | | 3x+-1=-5 | | 4D^2-11D+7=0 | | 2x+1-(-2)-(-x)=2-2x | | R=5w-15 | | F(x)=2x^2+11x+12 | | A=(2x+1)(4x-3) | | 4(p+5)=5(p-7) | | -3m+23-2(m-1)=9m-(6m-8)-5m+2 | | 7-(x-4)=8 | | -(9z-(14z+4))=4+(4z+1) | | q-3r-s=p | | 3(2x+3)-10x=7-(8x-2) | | (1/5)^-1 | | Kw^2-13x-5=0 | | (x+3)(x+3)+289=0 | | 5b+4=2b+11+5 |